(20S)‐Protopanaxadiol Ginsenosides Induced Cytotoxicity via Blockade of Autophagic Flux in HGC‐27 Cells. Issue 7 (29th June 2020) - Han, Qingqing; Han, Lijuan; Tie, Fangfang; Wang, Zhenhua; Ma, Chengjun; Li, Ji; Wang, Honglun; Li, Gang
Abstract: (20 S )‐Protopanaxadiol ginsenosides Rg3, Rh2 and PPD have been demonstrated for their anticancer activity. However, the underlying mechanism of their antitumor activity remains unclear. In the present study, we investigated the role of these three ginsenosides on cell proliferation and death of human gastric cancer cells (HGC‐27 cells). The sulforhodamine B (SRB) assay, Western blot analysis, fluorescence microscopy, confocal microscopy, high performance liquid chromatography (HPLC) analysis, flow cytometry, and transmission electron microscopy (TEM) were used to evaluate cell proliferation, apoptosis, and autophagy. The results showed that both Rh2 and PPD were more effective than Rg3 in inhibiting HGC‐27 cell proliferation and inducing cytoplasmic vacuolation, while no significant changes in apoptosis were observed. Interestingly, cytoplasmic vacuolation and blockade of autophagy flux were observed after treatment with Rh2 and PPD. Rh2 obviously up‐regulated the expression of the LC3II and p62. Furthermore, the increase in lysosomal pH and membrane rupture was observed in Rh2‐treated and PPD‐treated cells. When HGC‐27 cells were pretreated with bafilomycin A1, a specific inhibitor of endosomal acidification, cellular vacuolization was increased, and the cell viability was significantly decreased, which indicated that Rh2‐induced lysosome‐damage accelerated cell death. Furthermore, data derived from mitochondrial analysis showed that excessive mitochondrial reactive oxygen species (ROS) and dysregulation of mitochondrial energy metabolism were caused by Rh2 and PPD treatment in HGC‐27 cells. Taken together, these phenomena indicated that Rh2 and PPD inhibited HCG‐27 cells proliferation by inducing mitochondria damage, dysfunction of lysosomes, and blockade of autophagy flux. The number of glycosyl groups at C‐3 position could have an important effect on the cytotoxicity of Rg3, Rh2 and PPD. Abstract :